Polski wygnaniec. Teofil Lenartowicz w oczach Giovanniego Papiniego - Ślarzyńska, Małgorzata (Colloquia Litteraria, 2023)
This article focuses on giovanni Papini’s little-known short story L’esule polacco from the volume Passato remoto (1948) and the encounter between teofil Lenartowicz and the Italian writer described in it. The meeting between the teenage Papini, who was wandering with his father through the hills around Florence, and the elderly Polish poet, who had been in Italy for years, took place in 1892. Papini’s reminiscence evoked the most important elements of the characteristics of the figure and oeuvre of Lenartowicz, in whom the Italian writer immediately recognised a true poet. Papini’s reminiscence about of Lenartowicz left a trace in the perception of later Polish emigration in Italy, as evidenced by the recalled text by Leonardo kociemski. The article is accompanied by a translation of the short story L’esule polacco, previously not translated into Polish.